Refocusing Positively and its Relationship with (Analytic–Global) Cognitive Style Among University Students - Abd, Salwa Faiq (Journal of Educational and Psychological Sciences, 2024)
The research aimed to know the Refocusing Positively and (Analytic–Global) Cognitive Style among university students, as well as to identify the significance of the difference in the relationship according to the gender variable (males- females), as well as the correlational relationship between the two variables. In order to verify this, the researcher adopted The Refocusing Positively scale prepared by (Al-Maliki 2022) according to (Jarnowski model, 2001)., and it also adopted the (Analytic–Global) Cognitive Style prepared by (Shutb 2013) based on Kagan's theory (Kagan, 1963)., and their psychometric properties were confirmed. The two tools were applied to a sample of (160) male and female students, with (80) males and (80) females, as they were selected from (6) colleges at the University of Baghdad for the academic year 2023-2024. The results of the research showed the following: 1. The research sample possesses the characteristic of Refocusing Positively.2. The research sample possesses the analytical cognitive style. 3. There is no difference in the relationship between Refocusing Positively and cognitive style according to the gender variable (males and females). 4. The results of the statistical analysis showed that there is no significant correlation between the two variables of the current research. Based on the results, the researcher recommends the following: Increasing interest in educational programs that clarify the capabilities possessed by students and how to benefit from them correctly to develop cognitive methods among students.- Motivating university students by college deans and department heads to participate in courses held by research centers and service centers inside and outside the university that aim to develop the self and build the character of university students.
Keywords: Refocusing Positively; Cognitive style; University students